Spectral domain optical coherence tomography (SD OCT) pattern of macular edema and visual acuity in recent-onset branch retinal vein occlusion (BRVO) in a tertiary hospital - Shakya, Kiran; Pokhrel, Ram Prasad; Malla, Om Krishna (Journal of Kathmandu Medical College, 2018)
Background: Macular edema is the common sight-threatening condition following branch retinal vein occlusion.Objective: To find spectral domain optical coherence tomography characteristics of macular involvement and visual acuity in the patients with branch retinal vein occlusionMethodology: This is a cross-sectional study; consecutive new cases of branch retinal vein occlusion diagnosed at the ophthalmology department of Kathmandu Medical College, Kathmandu were carried out from November 2016 to October 2017. All subjects were divided three groups with normotensive/controlled hypertension, stage 1 hypertension (systolic pressure >140 mm Hg or diastolic pressure >90mm Hg) and Stage 2 hypertension (systolic pressure >160 mm Hg or diastolic pressure >100 mm Hg).The macular edema was evaluated by taking best corrected visual acuity and spectral domain optical coherence tomography for measurement of central foveal thickness.Results: Forty patients with forty eyes were enrolled. Mean age was 58.5 years SD ± 9.98 years. Stage 1 and stage 2 hypertensive groups had significantly worse best corrected visual acuity and more thickness of central foveal thickness than normotensive/controlled group (p